MODEL KEBERLANJUTAN USAHA PASCA PANDEMI MENGGUNAKAN METODE PENDEKATAN KEUANGAN DAN NON KEUANGAN (STUDI PADA UKM BAKPIA SLEMAN) - Utami, Lila Retnani; Sujarweni, Veronika Wiratna; Rahmayanti, Dian Rhesa; Nurhayati, Hesti (RJABM (Research Journal of Accounting and Business Management), 2022)
The pre-survey conducted by researchers on Bakpia SMEs in Sleman, the majority experienced a decline in sales which greatly impacted livelihoods. The purpose of this study is to develop a model of SME business sustainability from a financial and non-financial perspective, based on the Balance Scorecard theory and findings in the field. This type of research is qualitative case study. The object of this research is Bakpia SMEs in Sleman who were able to survive during the pandemic, Sleman bakpia consumers. The type of data used is primary and secondary. Sources of data obtained by means of interviews, observation and documentation, questionnaires.The result is that SMEs that can survive in the pandemic era are SMEs that have strength and make non-financial efforts to satisfy customers, innovate and operate products. UKM do growth and learning, give alms, help orphans. From a financial perspective, SMEs separate personal and business money, plan monthly income and expenses, prepare financial reports in the form of income statements and balance sheets. This UKM is proven in terms of economical, effective and efficient financial performance and has managed to get through the pandemic and currently 3 bakpia UKM have sales that are almost the same as before the pandemicKeywords: Post Pandemi Business Sustainability Model; SMEs; Bakpia